2016
DOI: 10.1111/cas.13005
|View full text |Cite
|
Sign up to set email alerts
|

IL‐17A‐producing CD30+ Vδ1 T cells drive inflammation‐induced cancer progression

Abstract: Although it has been suspected that inflammation is associated with increased tumor metastasis, the exact type of immune response required to initiate cancer progression and metastasis remains unknown. In this study, by using an in vivo tumor progression model in which low tumorigenic cancer cells acquire malignant metastatic phenotype after exposure to inflammation, we found that IL‐17A is a critical cue for escalating cancer cell malignancy. We further demonstrated that the length of exposure to an inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…The cytokine IL17A supports the tumor-promoting immune response and counteracts the antitumor function of IFNg (32)(33)(34). We found that NK-cell depletion did not affect the in vivo growth of MCA205-Luc2 cells in IL17A-deficient (IL17 KO) mice ( Fig.…”
Section: Il17a-neutrophil Axis Promoted Cancer Cell Growth In the Absmentioning
confidence: 73%
“…The cytokine IL17A supports the tumor-promoting immune response and counteracts the antitumor function of IFNg (32)(33)(34). We found that NK-cell depletion did not affect the in vivo growth of MCA205-Luc2 cells in IL17A-deficient (IL17 KO) mice ( Fig.…”
Section: Il17a-neutrophil Axis Promoted Cancer Cell Growth In the Absmentioning
confidence: 73%
“…Importantly, in human cancers, γδ17 T cells were also observed and associated with advanced stages of disease in colorectal and squamous cell skin tumors [ 13 , 14 ] and decreased survival of patients with gallbladder cancer [ 15 ]. Of note, the Vδ1 + subpopulation of human γδ T cells was reported to be a major source of IL-17 in colon cancer [ 13 ] and squamous cell skin cancer [ 14 ] patients and to promote inflammation-induced cancer progression [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vδ1 γδ T cells are another subgroup of recently discovered γδ T cells with protumor activity. Vδ1 γδ T cells are involved in inflammation-induced cancer progression, dependent on the production of IL-17A [ 73 ]. In another report, Vδ1 γδ T cells have been reported to strongly secrete TGF-β.…”
Section: γδ T Cells As Friends In Cancer Developmentmentioning
confidence: 99%